Repair method of back contact solar cell
By applying a high resistivity conductive material near the defect position of the back contact solar cell, the positive electrode and the negative electrode are connected to the negative electrode, the local heating or heat spot problem of the cell is solved, and the effective repair and performance improvement of the cell is achieved.
Patent Information
- Application Number
- CN202411980927.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Back contact with solar cells is prone to local heat or hot spot problems, resulting in excessive battery height and permanent and irreversible damage, which makes it difficult to re-repair.
By applying a conductive material between the positive electrode and the negative electrode adjacent to the defect position of the cell, a conductive connection is formed, and the resistivity of the conductive material is greater than 0.5 mΩ•cm to reduce the reverse breakdown voltage and improve the heat spot problem.
This method can improve or eliminate heat spot defects, and the process is simple. The repaired battery cells can be directly used for the processing and production of battery modules, which improves the comprehensive yield of solar cell production and effectively reduces production costs.
Smart Images

Figure CN119866092A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaics, and in particular relates to a method for repairing a back-contact solar cell. Background Art
[0002] Back-contact solar cells have broad application prospects due to their higher photoelectric conversion efficiency. Back-contact solar cells are cells in which both the emitter and base contact electrodes are placed on the back side of the cell (non-light-receiving side). The light-receiving side of the cell is not blocked by any metal electrode, which effectively increases the short-circuit current of the cell.
[0003] Due to the difficulty of back-contact solar cell technology and the complex process steps, it is easy to have various performance problems during the preparation process. Some performance problems can be discovered and reworked during the preparation process; some performance problems (such as microcracks and hot spots) cannot be discovered during the preparation process and can only be screened out during the finished product inspection after all processes are completed. Since the finished product has been metallized, it is necessary to use a strong acid solution to remove the metal electrode before rework, which has a high processing cost and is not environmentally friendly.
[0004] When solar cells are connected in series, the total output current is the value of the smallest cell, and the total output voltage is the sum of the voltages of each cell. Once one cell current is smaller than the other cells, because the output current will take the minimum value of all individual cells, the current of other cells in the entire series circuit will also decrease, thereby greatly reducing the output power of the entire circuit. When one of the cells in a string of cells is shaded, the current of the good cell is reduced, and the extra current generated by the good cell makes the good cell forward biased. If the series battery string is short-circuited, the forward bias across these good cells will reverse bias the shaded cell. When many series currents cause a large reverse bias on the cells shaded by the shadow, it is easy to cause a large heat dissipation on the poor cell, and a hot spot occurs. Inevitably, all the power generation capacity on the good cell is dissipated on the poor cell. A large amount of power dissipation on the same area causes local heating of the cell or the appearance of a hot spot, which further causes the temperature of the cell to reach 150°C, which can cause permanent and irreversible damage, such as the breakage of the cell or glass, the melting of the solder, or the attenuation and degradation of the cell.
[0005] Hot spot problem is a problem that is very easy to occur in the battery production process, and accounts for a high proportion of defective battery cells. Statistics show that hot spot problem is the most important failure mode in photovoltaic modules installed in the past fifteen years. Therefore, a novel solar cell processing technology is urgently needed to improve the performance of solar cells and increase the overall yield of solar cell production. Summary of the invention
[0006] The present invention aims to overcome the defects in the prior art that back-contact solar cells are prone to local heating or hot spots, which causes the cell height to be too high, resulting in permanent and irreversible damage and making it difficult to repair. A back-contact solar cell repair method is provided to overcome the above defects.
[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: A method for repairing a back contact solar cell comprises the following steps: Detect defective solar cells and locate the defective locations; A conductive material is applied between the positive electrode and the negative electrode adjacent to the defective position of the battery cell to connect the positive electrode and the negative electrode, thereby forming a conductive connection, wherein the resistivity of the conductive material is greater than 0.5 mΩ•cm.
[0008] Solar cells with common hot spot defects cannot be used as components and can only be scrapped or reworked. Since the cell has undergone a metallization step, it is necessary to first use a strong acid solution to remove the metal electrode and then clean and rework it, and the processing steps are very cumbersome. Even if it is reworked and processed into a cell, the performance of the cell is poor. Since a high-resistance conductive connection is achieved between the positive and negative electrodes near the hot spot defect on the solar cell, the reverse breakdown voltage of the solar cell can be effectively reduced, thereby improving or eliminating the hot spot problem of the cell. Based on this, the present invention utilizes local repair treatment of defective solar cells to make the local high-resistance conduction of the positive and negative electrodes near the defect to improve battery performance, so that unusable hot spot cells can be reused. The repair treatment method of the present invention only needs to apply a conductive material near the hot spot defect on the cell to connect the positive and negative electrodes, so as to improve or eliminate the hot spot defect. The process is simple, and the repaired cell can be directly used for the processing and production of battery components, which improves the comprehensive yield of solar cell production and effectively reduces production costs. The resistivity of the conductive material of the present invention is greater than 0.5 mΩ•cm, and the use of high resistance connection helps to ensure that the positive electrode and the negative electrode adjacent to the defective position are in a connected state, thereby effectively reducing the reverse breakdown voltage. At the same time, it can effectively avoid the use of low resistance connection to cause significant leakage between the positive electrode and the negative electrode adjacent to the defective position, thereby reducing the impact on the performance of the battery cell.
[0009] Preferably, a hot spot test is performed on defective solar cells, the solar cells are photographed and screened by an infrared thermal imager, and the defective positions on the cells are marked according to the corresponding heating areas on the infrared thermal imager.
[0010] As a further preference, hot spot tests and electroluminescence tests are performed on defective solar cells respectively, and the solar cells are photographed by an infrared thermal imager to obtain an infrared image of the cell and compare it with the electroluminescence (EL) test image to locate the defect position on the cell.
[0011] Through the hot spot test, an infrared thermal imager is used to achieve non-contact temperature measurement of solar cells, so that the cells can be fully scanned in a short time and areas with abnormally high local temperatures on the cells can be quickly discovered, which helps to improve detection efficiency, reduce detection costs, and improve detection accuracy, effectively avoiding the subjectivity and inaccuracy of human judgment.
[0012] Preferably, the conductive connection is formed by directly forming the conductive connection or forming the conductive connection after treatment.
[0013] The method of directly forming a conductive connection is simple and fast, efficient and time-saving, and can achieve precise construction, which helps to reduce costs. At the same time, it helps to reduce failure points and reduce signal attenuation and delay, thereby improving conductivity. The method of forming a conductive connection after treatment helps to enhance the strength of the connection part, making it more solid and not easy to fall off. It also helps to adapt to different materials, expand the scope of application, and improve connection accuracy.
[0014] Preferably, the conductive material directly forming the conductive connection is any one or more combinations of metal ceramic resistor film materials, metal compound film materials, and non-metal film materials.
[0015] Metal ceramic resistor film materials have the advantages of high resistivity and high temperature resistance, high stability, and can maintain stable resistance values over a wide temperature range. Metal compound film materials have good electrical conductivity and mechanical properties, which can meet the requirements of electronic devices for conductive connections. At the same time, they have excellent corrosion resistance and can be used for a long time in harsh environments without performance degradation. Non-metallic film materials are usually lighter and have a certain degree of flexibility, which has advantages in situations where lightweight and flexible connections are required. Using the above materials as conductive materials to directly form conductive connections helps to improve the reliability of conductive connections and maintain the performance of conductive connections, thereby reducing production costs.
[0016] As a further preference, the metal ceramic resistor film material is composed of a mixture of metal and oxide insulator, the metal is any one or more combination of silver, copper, zinc, tin, magnesium, aluminum, nickel, cobalt, chromium, tantalum, and ruthenium, and the oxide insulator is any one or more combination of silicon oxide, aluminum oxide, and calcium oxide.
[0017] As a further preferred embodiment, the metal compound film material is tantalum nitride (TaN), tungsten oxide, Ti2 O 5 、V 2 O 5 、LaTiO 3 、CaVO 3 、SnOx、NbO、PbO 2 、MnO 2 Any one or more combinations of .
[0018] As a further preference, the non-metallic thin film material is a carbon material, and the resistivity of the carbon material is 3-60 mΩ•cm.
[0019] Preferably, the conductive material is applied in the process of directly forming a conductive connection by any one or more combinations of 3D printing, laser transfer, selective laser sintering (SLS), laser selective melting (SLM), directed energy deposition (DED), material jetting, and reduction photopolymerization technology.
[0020] Preferably, the conductive material that forms the conductive connection after being processed is a high-resistance conductive paste.
[0021] Preferably, the conductive material forming the conductive connection needs to be subjected to a heat treatment or an energy curing treatment.
[0022] The conductive material forming the conductive connection is heat treated, which helps to optimize the microstructure of the conductive material, thereby improving the mobility of electrons and enhancing the conductive performance. It also helps to reduce defects inside the material, thereby improving the purity of the material. The conductive material forming the conductive connection is energy cured, which helps to form a stable conductive network, thereby improving the conductive performance. It can also make the surface of the conductive material flatter and smoother, reduce the surface resistance, and further improve the conductive performance. In addition, after heat treatment or energy curing treatment, the connection strength between the conductive material and the positive and negative electrodes adjacent to the defect position can be effectively enhanced, thereby reducing failures caused by poor connection.
[0023] As a further preference, the heat treatment is infrared fast-firing furnace sintering or laser sintering, and the energy curing treatment is any one or more combinations of thermal curing, photocuring, and electron beam curing.
[0024] Preferably, the high-resistance conductive paste is applied by any one or more combinations of coating, spraying, direct paste writing, and dispensing.
[0025] As a further preference, the spraying is directional spraying, the viscosity of the sprayed high-resistance conductive paste is 10~100cps; the viscosity of the dispensed high-resistance conductive paste is 2000~10000cps; the applied high-resistance conductive paste is in liquid, colloidal, semi-solid or non-Newtonian fluid state.
[0026] Preferably, the high-resistance conductive paste is a composition including conductive metal particles and a polymer adhesive, the mass of the conductive metal particles accounts for 1-25% of the mass of the high-resistance conductive paste, and the polymer adhesive is a combination of any one or more of ethylene-vinyl acetate copolymer, polyolefin resin, epoxy resin, polyurethane resin, acrylic resin, and silicone resin, and the mass of the polymer adhesive accounts for 10-50% of the mass of the high-resistance conductive paste.
[0027] As further preferred, the conductive metal particles are any one or more combinations of silver, aluminum, copper, nickel, silver-coated copper, and nickel.
[0028] Preferably, the high-resistance conductive paste further comprises an inorganic binder, the mass of the inorganic binder accounts for 30-50% of the mass of the high-resistance conductive paste, and the inorganic binder is TeO 2 、PbO、Bi 2 O 3 , WO 3 、ZnO、SiO 2 、Na 2 O. Li 2 O、Al 2 O 3 , CuO, TiO 2 、MoO 3 Any combination of two or more of the following; The high-resistance conductive paste further comprises a solvent, and the solvent is any one of water and an organic solvent or a combination of the two, and the boiling point of the solvent is ≥100°C.
[0029] Inorganic adhesives can provide good adhesion and help improve the adhesion of conductive pastes. They can form a strong bond with the surface of the cell during the heat treatment process, thereby forming a stable and reliable conductive connection and reducing failures caused by poor connections. At the same time, inorganic adhesives can enhance the stability of the paste and effectively prevent the paste from stratification and precipitation during long-term storage or use, thereby ensuring stable and reliable performance of the conductive connection. In addition, the TeO contained in the inorganic adhesive 2 、PbO、Bi 2 O 3 The materials themselves have a high resistivity and can effectively increase the overall resistance value of the slurry.
[0030] High-resistance conductive pastes contain solvents with high boiling points (boiling point ≥ 100°C), which can effectively prevent changes in paste properties caused by solvent volatilization and help maintain the stability of the paste. At the same time, the viscosity of the paste can also be adjusted to ensure that the paste can be evenly coated on the substrate. In addition, high-boiling-point organic solvents can enhance dispersibility and make the paste more uniform and stable.
[0031] As further preferred, the solvent is any one or more combinations of water, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, diethylene glycol monobutyl ether, ethylene glycol methyl ether acetate, methyl lactate, ethyl lactate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, dipropylene glycol methyl ether acetate, γ-butyrolactone, terpineol, ethyl acetoacetate, N-methylpyrrolidone, N,N-dimethylimidazolidinone, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, xylene, propylene glycol tert-butyl ether, acetylacetone, propylene glycol n-butyl ether or 3-methoxy-3-methylbutanol.
[0032] Therefore, the present invention has the following beneficial effects: (1) The present invention utilizes local repair processing of defective solar cells to make the local high resistance of the positive and negative electrodes near the defects conduction to improve the battery performance, and promote the reuse of unusable hot spot cells; (2) The repair method of the present invention only needs to apply a conductive material near the hot spot defect on the cell to connect the positive electrode and the negative electrode, so as to improve or eliminate the hot spot defect. The process is simple, and the repaired cell can be directly used for the processing and manufacturing of battery components, thereby improving the comprehensive yield of solar cell production and effectively reducing production costs; (3) The resistivity of the conductive material of the present invention is greater than 0.5 mΩ•cm. The use of high resistance connection helps to ensure that the positive electrode and the negative electrode adjacent to the defective position are in a connected state, thereby effectively reducing the reverse breakdown voltage. At the same time, it can effectively avoid the use of low resistance connection to cause significant leakage between the positive electrode and the negative electrode adjacent to the defective position, thereby reducing the impact on the performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of a back-contact solar cell structure in Example 1.
[0034] Figure 2 This is a schematic diagram of a back-contact solar cell structure in Example 2.
[0035] Figure 3 This is a schematic diagram of the structure of the defect location on the back side of the solar cell being repaired in Example 1. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0037] Example A method for repairing a back contact solar cell comprises the following steps: Detect defective solar cells and locate the defective locations; A conductive material is applied between the positive electrode and the negative electrode adjacent to the defective position of the battery cell to connect the positive electrode and the negative electrode, thereby forming a conductive connection, wherein the resistivity of the conductive material is greater than 0.5 mΩ•cm.
[0038] Hot spot test is performed on back-contact solar cells. The hot spot test is to connect a reverse voltage (e.g. -12V) to the cell to make it in a reverse bias state, and then use an infrared thermal imager to capture the temperature rise of the cell. By comparing the temperature changes of the cell, the cells that are above the initial temperature (Baseline temperature) (3°C or 5°C) are selected, and the corresponding position of the heating area on the cell that appears on the infrared thermal imager is marked. Since the heating area may be a large area, in order to accurately locate the location of the defect on the solar cell, the defective solar cell can be subjected to hot spot test and electroluminescence test respectively, and then the infrared image of the cell taken by the infrared thermal imager is compared with the electroluminescence test (EL test) image to determine the type of defect on the solar cell, the specific location and other detailed information. The defects that cause hot spots on solar cells may be broken grids, hidden cracks or black edges, etc. These defects can be found on the EL image.
[0039] Through the hot spot test, an infrared thermal imager is used to achieve non-contact temperature measurement of solar cells, so that the cells can be fully scanned in a short time and areas with abnormally high local temperatures on the cells can be quickly discovered, which helps to improve detection efficiency, reduce detection costs, and improve detection accuracy, effectively avoiding the subjectivity and inaccuracy of human judgment.
[0040] A conductive material is applied between the positive electrode and the negative electrode near the defective position of the cell to connect the positive electrode and the negative electrode, thereby forming a conductive connection. The purpose of this repair process is to connect the positive electrode and the negative electrode near the defective position on the cell, forming a diode with a relatively low reverse breakdown voltage at the connection, which is conducive to causing the solar cell to have a relatively low reverse breakdown voltage when it is shaded.
[0041] As an implementation method, the applied conductive material is a resistor material with a certain resistivity. It can directly form a conductive connection after application, or form a conductive connection after application and treatment. The method of directly forming a conductive connection is simple and fast, efficient and time-saving, and can achieve precise construction, which helps to reduce costs. At the same time, it helps to reduce fault points and reduce signal attenuation and delay, thereby improving the conductive performance. The method of forming a conductive connection after treatment helps to enhance the strength of the connection part, making it more firm and not easy to fall off. It also helps to adapt to different materials, expand the scope of application, and improve connection accuracy.
[0042] As an implementation method, the resistivity of the applied conductive material needs to be greater than 0.5 mΩ•cm. The use of high resistance connection helps to ensure that the positive electrode and the negative electrode adjacent to the defective position are in a connected state, thereby effectively reducing the reverse breakdown voltage. At the same time, it can effectively avoid the use of low resistance connection to cause significant leakage between the positive electrode and the negative electrode adjacent to the defective position, thereby reducing the impact on the performance of the battery cell.
[0043] As an implementation mode, the conductive material that can directly form a conductive connection after being applied is any one or more combinations of metal ceramic resistor film materials, metal compound film materials, and non-metal film materials.
[0044] Metal ceramic resistor film materials have the advantages of high resistivity and high temperature resistance, high stability, and can maintain a stable resistance value over a wide temperature range. Metal compound film materials have good electrical conductivity and mechanical properties, which can meet the requirements of electronic devices for conductive connections. At the same time, they have excellent corrosion resistance and can be used for a long time in harsh environments without performance degradation. Non-metallic film materials are usually light and have certain flexibility, which has advantages in situations where lightweight and flexible connections are required. Using the above materials as conductive materials to directly form conductive connections helps to improve the reliability of conductive connections and maintain the performance of conductive connections, thereby reducing production costs. After the above materials are applied between the positive and negative electrodes on the surface of the battery cell, no treatment is required to form a conductive connection. The process is simple and precise construction can be achieved.
[0045] As another embodiment, the metal ceramic resistor film material is composed of a mixture of metal and oxide insulator, wherein the metal is any one or more combinations of silver, copper, zinc, tin, magnesium, aluminum, nickel, cobalt, chromium, tantalum, and ruthenium, and the oxide insulator is any one or more combinations of silicon oxide, aluminum oxide, and calcium oxide.
[0046] As another embodiment, the metal compound film material is tantalum nitride (TaN), tungsten oxide, Ti 2 O 5 、V 2 O5 、LaTiO 3 、CaVO 3 、SnOx、NbO、PbO 2 、MnO 2 Any one or more combinations of .
[0047] As another implementation, the non-metallic film material is a carbon material, and the resistivity of the carbon material is 3-60 mΩ•cm.
[0048] As an embodiment, the conductive material is applied in the process of directly forming a conductive connection by any one or more combinations of 3D printing, laser transfer, selective laser sintering (SLS), laser selective melting (SLM), directed energy deposition (DED), material jetting, and v-photopolymerization technology.
[0049] As an embodiment, the conductive material that needs to be processed after application to form a conductive connection is a high-resistance conductive paste.
[0050] As an implementation mode, the conductive material that needs to be processed to form a conductive connection needs to be heat treated or energy cured.
[0051] The conductive material forming the conductive connection is heat treated, which helps to optimize the microstructure of the conductive material, thereby improving the mobility of electrons and enhancing the conductive performance. It also helps to reduce defects inside the material, thereby improving the purity of the material. The conductive material forming the conductive connection is energy cured, which helps to form a stable conductive network, thereby improving the conductive performance. It can also make the surface of the conductive material flatter and smoother, reduce the surface resistance, and further improve the conductive performance. In addition, after heat treatment or energy curing treatment, the connection strength between the conductive material and the positive and negative electrodes adjacent to the defect position can be effectively enhanced, thereby reducing failures caused by poor connection.
[0052] As another embodiment, the heat treatment is infrared fast sintering furnace sintering or laser sintering. Preferably, the heat treatment method is laser sintering, because laser sintering can achieve rapid sintering of local positions. Energy curing treatment is any one or more combinations of thermal curing, photocuring, and electron beam curing.
[0053] As an implementation manner, the high-resistance conductive paste is applied by any one or more combinations of coating, spraying, direct ink writing (DIW), and dispensing.
[0054] As another embodiment, the spraying is directional spraying, and the viscosity of the sprayed high-resistance conductive paste is 10-100 cps. The viscosity of the dispensed high-resistance conductive paste is 2000-10000 cps. The applied high-resistance conductive paste is in a liquid, colloidal, semi-solid or non-Newtonian fluid state.
[0055] As an embodiment, the high-resistance conductive paste is a composition including conductive metal particles and a polymer binder. The mass of the conductive metal particles accounts for 1-25% of the mass of the high-resistance conductive paste. The polymer binder is a combination of any one or more of ethylene-vinyl acetate copolymer, polyolefin resin, epoxy resin, polyurethane resin, acrylic resin, and silicone resin. The mass of the polymer binder accounts for 10-50% of the mass of the high-resistance conductive paste.
[0056] As another embodiment, the conductive metal particles are any one or more combinations of silver, aluminum, copper, nickel, silver-coated copper, and nickel.
[0057] As an embodiment, the high-resistance conductive paste further includes an inorganic binder, and the mass of the inorganic binder accounts for 30-50% of the mass of the high-resistance conductive paste. The inorganic binder is TeO 2 、PbO、Bi 2 O 3 , WO 3 、ZnO、SiO 2 、Na 2 O. Li 2 O、Al 2 O 3 , CuO, TiO 2 、MoO 3 Any combination of two or more of .
[0058] Inorganic adhesives can provide good adhesion and help improve the adhesion of conductive pastes. They can form a strong bond with the surface of the cell during the heat treatment process, thereby forming a stable and reliable conductive connection and reducing failures caused by poor connections. At the same time, inorganic adhesives can enhance the stability of the paste and effectively prevent the paste from stratification and precipitation during long-term storage or use, thereby ensuring stable and reliable performance of the conductive connection. In addition, the TeO contained in the inorganic adhesive 2 、PbO、Bi 2 O 3 The materials themselves have a high resistivity and can effectively increase the overall resistance value of the slurry.
[0059] As an embodiment, the high-resistance conductive paste further includes a solvent, and the solvent is any one of water and an organic solvent or a combination of the two. In order to improve the workability, the boiling point of the solvent is preferably ≥100°C.
[0060] High-resistance conductive pastes contain solvents with high boiling points (boiling point ≥ 100°C), which can effectively prevent changes in paste properties caused by solvent volatilization and help maintain the stability of the paste. At the same time, the viscosity of the paste can also be adjusted to ensure that the paste can be evenly coated on the substrate. In addition, high-boiling-point organic solvents can enhance dispersibility and make the paste more uniform and stable.
[0061] As another embodiment, the solvent is water, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, diethylene glycol monobutyl ether, ethylene glycol methyl ether acetate, methyl lactate, ethyl lactate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, dipropylene glycol methyl ether acetate, γ-butyrolactone, terpineol, ethyl acetoacetate, N-methylpyrrolidone, N,N-dimethylimidazolidinone, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, xylene, propylene glycol tert-butyl ether, acetylacetone, propylene glycol n-butyl ether or 3-methoxy-3-methylbutanol. Any one or more combinations thereof.
[0062] As an implementation method, for hot spot areas with larger or more dispersed hot spots on the battery cell, more than one repair connection can be set on the isolation area on the surface of the battery cell to provide multiple current paths to make the temperature distribution on the surface of the battery cell more uniform.
[0063] Example 1 like Figure 1 As shown, in this embodiment, a back contact solar cell structure is provided, wherein the substrate is an n-type or p-type single crystal silicon wafer, a p-type doped region and an n-type doped region are arranged on the back side of the silicon substrate, the p-type doped region can be formed by doping with a dopant containing a P-type dopant (e.g., boron) in a local area on the back side of the silicon substrate, and the n-type doped region can be formed by doping with a dopant containing an N-type dopant (e.g., phosphorus) in a local area on the back side of the silicon substrate. The p-type doped region and the n-type doped region are alternately distributed on the back side of the silicon substrate and separated by an isolation region, which is a silicon substrate that is not additionally doped.
[0064] Silicon nitride is deposited on the back side of the silicon substrate to form a passivation layer. Silicon nitride preferably has a relatively large positive fixed charge density to keep the silicon surface below the trench in an accumulation state and provide good surface passivation. As an embodiment, silicon nitride is formed by a plasma enhanced chemical vapor deposition (PECVD) method to a thickness of about 40 to 100 nm.
[0065] The p-type metal electrode and the n-type metal electrode can pass through the silicon nitride to be electrically connected to the p-type doping region and the n-type doping region respectively.
[0066] The passivation anti-reflection layer is deposited by ALD with 4~8nm Al2 O 3 , and then use PECVD to deposit about 80nm of silicon nitride.
[0067] This embodiment provides a method for repairing a back-contact solar cell as described above.
[0068] like Figure 3 As shown, a method for repairing a back contact solar cell comprises the following steps: Under the condition of -12V reverse bias, the defective solar cell was tested for hot spots. The temperature rise of the cell was photographed by an infrared thermal imager. The temperature change of the cell was compared, and the cells that were higher than the initial temperature (Baseline temperature) (3°C or 5°C) were selected and marked with the corresponding position of the heating area on the cell on the infrared thermal imager, so as to locate the defect. The temperature of the defective part of the solar cell before the inspection was 27.3°C.
[0069] Carbon material is 3D printed between the positive and negative electrodes (i.e., p-type and n-type electrodes) adjacent to the defective position of the solar cell to connect the adjacent positive and negative electrodes, thereby directly forming a conductive connection. The resistivity of the applied carbon material is 5mΩ•cm. After the repair connection is completed, the defective position of the solar cell is inspected again, and the temperature rise of the cell is photographed by an infrared thermal imager. The results show that the temperature at the defective position of the solar cell after the repair connection is 23.1℃.
[0070] Through repair, the temperature of the solar cell at the defect is significantly reduced, indicating that the p-type doping area and the n-type doping area of the solar cell are electrically coupled through the conductive material, and have a relatively low reverse breakdown voltage. When the solar cell is shaded, it can improve the safety of the cell and the module.
[0071] Example 2 The difference between this embodiment and embodiment 1 is that: The back contact solar cell structure provided in this embodiment is different. Figure 2 As shown, a back contact solar cell structure, wherein the substrate is an n-type or p-type single crystal silicon wafer, and the p-type doped region and the n-type doped region are arranged on the back side of the silicon substrate. The p-type doped region and the n-type doped region are formed on a tunneling layer, and the tunneling layer includes silicon dioxide thermally grown on the surface of the silicon substrate or an ultra-thin silicon dioxide layer deposited on the silicon substrate, with a thickness of 0.5nm to 5nm. The tunneling layer may also include silicon nitride, aluminum oxide, and silicon oxynitride.
[0072] Silicon nitride is deposited on the back side of the silicon substrate to form a passivation layer. Silicon nitride preferably has a relatively large positive fixed charge density to keep the silicon surface below the trench in an accumulation state and provide good surface passivation. As an embodiment, silicon nitride is formed by a plasma enhanced chemical vapor deposition (PECVD) method to a thickness of about 40 to 100 nm.
[0073] The p-type metal electrode and the n-type metal electrode can pass through the silicon nitride to be electrically connected to the p-type doping region and the n-type doping region respectively.
[0074] This embodiment also provides a method for repairing the back contact solar cell as described above.
[0075] A method for repairing a back contact solar cell comprises the following steps: Under the condition of -12V reverse bias, the defective solar cell was tested for hot spots. The temperature rise of the cell was photographed by an infrared thermal imager. The temperature change of the cell was compared, and the cells that were higher than the initial temperature (Baseline temperature) (3°C or 5°C) were selected and marked with the corresponding position of the heating area on the cell on the infrared thermal imager, so as to locate the defect. The temperature of the defective part of the solar cell before the inspection was 28.6°C.
[0076] Nickel conductive paste is dispensed between the positive and negative electrodes (i.e., p-type electrode and n-type electrode) adjacent to the defective position of the solar cell to connect the adjacent positive and negative electrodes, and a conductive connection is formed after laser heat treatment (i.e., laser sintering). The resistivity of the nickel conductive paste after laser heat treatment is 3mΩ•cm. Among them, the viscosity of the colloidal nickel conductive paste is 5000cps. The nickel conductive paste is a composition including nickel conductive particles and a polymer adhesive. Nickel conductive particles account for 70% of the mass of the nickel conductive paste. The polymer adhesive is an acrylic resin, and the mass of the acrylic resin polymer adhesive accounts for 12% of the mass of the nickel conductive paste. The nickel conductive paste also includes an inorganic adhesive, and the mass of the inorganic adhesive accounts for 10% of the mass of the nickel conductive paste. The inorganic adhesive is PbO, Bi 2 O 3 、ZnO、SiO 2 , Li 2 The nickel conductive paste also includes a solvent, the mass of the solvent accounts for 8% of the mass of the nickel conductive paste, and the solvent is diethylene glycol monobutyl ether.
[0077] Through repair, the temperature of the solar cell at the defect is significantly reduced, indicating that the p-type doping area and the n-type doping area of the solar cell are electrically coupled through the conductive material, and have a relatively low reverse breakdown voltage. When the solar cell is shaded, it can improve the safety of the cell and the module.
[0078] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.
Claims
1. A method for repairing a back contact solar cell, characterized in that: The following steps are involved: Detect defective solar cells and locate the defective locations; A conductive material is applied between the positive electrode and the negative electrode adjacent to the defective position of the battery cell to connect the positive electrode and the negative electrode, thereby forming a conductive connection, wherein the resistivity of the conductive material is greater than 0.5 mΩ•cm.
2. A method for repairing a back contact solar cell according to claim 1, characterized in that: Conduct hot spot tests on defective solar cells, photograph and screen the solar cells using an infrared thermal imager, and mark the defective locations on the cells according to the corresponding heating areas on the infrared thermal imager.
3. The method for repairing a back contact solar cell according to claim 1, characterized in that: The conductive connection is formed by directly forming the conductive connection or by forming the conductive connection after treatment.
4. The method for repairing a back contact solar cell according to claim 3, characterized in that: The conductive material directly forming the conductive connection is any one or more combinations of metal ceramic resistor film materials, metal compound film materials, and non-metal film materials.
5. A method for repairing a back contact solar cell according to claim 3 or 4, characterized in that: The conductive material is applied in the process of directly forming a conductive connection by any one or more combinations of 3D printing, laser transfer, selective laser sintering, laser selective melting, directed energy deposition, material jetting, and reduction photopolymerization technology.
6. The method for repairing a back contact solar cell according to claim 3, characterized in that: The conductive material that forms the conductive connection after being processed is a high-resistance conductive paste.
7. A method for repairing a back contact solar cell according to claim 6, characterized in that: The conductive material that forms the conductive connection needs to be cured by heat or energy.
8. The method for repairing a back contact solar cell according to claim 6, characterized in that: The high-resistance conductive paste is applied by coating, spraying, direct writing of paste, and dispensing, or any one or more combinations thereof.
9. A method for repairing a back contact solar cell according to claim 6 or 8, characterized in that: The high-resistance conductive paste is a composition including conductive metal particles and a polymer adhesive, the mass of the conductive metal particles accounts for 1-25% of the mass of the high-resistance conductive paste, the polymer adhesive is a combination of any one or more of ethylene-vinyl acetate copolymer, polyolefin resin, epoxy resin, polyurethane resin, acrylic resin, and silicone resin, and the mass of the polymer adhesive accounts for 10-50% of the mass of the high-resistance conductive paste.
10. A method for repairing a back contact solar cell according to claim 9, characterized in that: The high-resistance conductive paste further includes an inorganic binder, the mass of the inorganic binder accounts for 30-50% of the mass of the high-resistance conductive paste, and the inorganic binder is a combination of any two or more of TeO2, PbO, Bi2O3, WO3, ZnO, SiO2, Na2O, Li2O, Al2O3, CuO, TiO2, and MoO3; The high-resistance conductive paste further comprises a solvent, and the solvent is any one of water and an organic solvent or a combination of the two, and the boiling point of the solvent is ≥100°C.
Citation Information
Patent Citations
Solar cell and method for repairing cracks of solar cell
CN102867861A
Method and equipment for processing hot spot defect of battery piece, battery piece and photovoltaic module
CN118538825A
Thin-film solar cell
JP2006005020A
Method and device for manufacturing solar cell module
JP2009141056A